Method for rapid detection of alcohol and acetic acid concentration using light-responsive polymers and their composites
By immersing the photoresponsive polymer or its liquid crystal composite film in different concentrations of alcohol or acetic acid solution, the problem of distinguishing and identifying alcohol and acetic acid solutions in the prior art is solved. It realizes high sensitivity concentration detection, suitable for industrial applications.
Patent Information
- Application Number
- CN202210098790.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-27
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-01-27
AI Technical Summary
The prior art is difficult to distinguish and identify different concentrations of alcohol and acetic acid solutions through simple and easy methods, especially detection methods that lack sensitivity when the alcohol concentration is low.
Using a photoresponsive polymer or its liquid crystal composite film, the grating structure is used to soak in alcohol or acetic acid solution at different concentrations and observe the color difference in surface structure. Combined with light patterning and pre-lighting steps, the distinction between alcohol and acetic acid concentration and Identification.
It realizes high sensitivity detection of solutions of different concentrations, and can accurately distinguish alcohol concentrations as low as 1%. It is simple to operate and does not require complex system devices. It is suitable for industrial-scale promotion.
Smart Images

Figure CN114544609B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the application of a photoresponsive polymer and a composite thereof with liquid crystal small molecules in alcohol and acetic acid concentration detection technology. The present invention is a method for distinguishing and identifying solutions of different concentrations based on that the surface micro-nano structure of a film of the polymer or its composite presents different structural colors after being immersed in alcohol or acetic acid of different concentrations for the same time, and the surface morphology is controlled by utilizing the immersion time. Background Art
[0002] As a smart material, photoresponsive polymers can be remotely and precisely controlled, and can change the molecular structure and polymer chain structure properties without complex regulation systems, thereby changing the color, phase state, solubility, refractive index, and glass transition temperature (T g ) and other macroscopic features change. Photoresponsive polymers and their composites can be used to prepare complex surface micro-nano structures on a large scale, which can be applied in the fields of pattern display, information encryption and anti-counterfeiting, and optical device preparation.
[0003] Typical photoresponsive polymers include azobenzene, stilbene, Schiff base, spiropyran, etc., which can all isomerize under light. Among them, azobenzene derivatives are the most widely used in the field of light-controlled surfaces. In Chinese invention patent applications CN202010135620.1 and CN202111434432.X, a phenomenon of solvent-induced mass migration of azobenzene homopolymers and their liquid crystal small molecule complexes to form surface undulation gratings has been reported. By reducing T g Combined with the coordinated movement of liquid crystal molecules, in the solvent vapor atmosphere, the liquid crystal composite can produce larger surface fluctuations than the homopolymer at the same time, and the mass migration rate is faster. In addition, by adjusting the addition ratio of liquid crystal small molecules and the width of the light patterning slit, mass migration in different directions can be achieved on the same surface, thereby preparing complex and diverse surface micro-nano structures.
[0004] In the traditional sense, surface micro-nano structures are more often used in the production of complex optical components. From lens microarrays to optical masks, from photoresists to photodetectors, from large instruments used for mass production of precision instruments to small chips for daily electronic devices, all rely on surface structures without exception. However, linking the macroscopic phenomenon reflected by periodic surface micro-nano structures - structural colors visible to the naked eye - with alcohol and acetic acid concentration detection to distinguish and identify solutions of different concentrations has rarely been reported so far, and is a novel and meaningful research direction. This simple, easy, convenient and fast concentration detection method can directly see the effect at a certain observation angle without the help of other equipment, and is more practical than other dedicated detection devices. Summary of the invention
[0005] The present invention aims to provide a method for detecting the concentration of alcohol and acetic acid using a photoresponsive polymer or a complex thereof with liquid crystal small molecules. The method distinguishes solutions of different concentrations by observing the difference in structural color on the surface of a polymer or a liquid crystal composite film after being immersed in an alcohol or acetic acid solution for a certain period of time. More importantly, for alcohol concentration detection, when the alcohol concentration is as low as 1% by volume of ethanol, the response result is still different from that of pure water, indicating that the method has high sensitivity when used for alcohol detection.
[0006] The method for detecting the concentration of alcohol and acetic acid proposed in the present invention first requires an optical mask containing a grating structure. The mask usually needs to evaporate a chromium layer with a thickness of tens of nanometers on the surface of quartz glass to form a light-shielding layer, and then the light-shielding layer and the light-transmitting slits are arranged alternately and periodically to finally obtain a grating structure. The light-transmitting part of the mask can transmit most of the ultraviolet light and visible light, while the light-shielding part can completely block the ultraviolet light and visible light. By utilizing the interference and diffraction phenomena of the grating, the stripe pattern can be written on the surface of the polymer or its liquid crystal composite film. After the pattern is written, it can be immersed in alcohol or acetic acid solutions of different concentrations, taken out after a specified time, and observed immediately after the surface solvent is dried, and the volume fraction of ethanol or acetic acid in the solution can be obtained by structural color difference analysis.
[0007] The liquid crystal small molecules involved in the present invention are liquid crystal molecules widely used in commerce, including but not limited to room temperature liquid crystal 4-cyano-4'-pentylbiphenyl (5CB), 4-cyano-4'-octylbiphenyl (8CB), etc. The photoresponsive polymer refers to a class of polymers such as azobenzene, stilbene, Schiff base, spiropyran, etc. that can undergo cis-trans isomerization under light of a certain wavelength, as shown in Formula I to Formula IV:
[0008]
[0009] In the azobenzene photoresponsive polymer shown in formula I, the distilbene photoresponsive polymer shown in formula II, the Schiff base photoresponsive polymer shown in formula III, and the spiropyran photoresponsive polymer shown in formula IV, R1 is a hydrogen atom or a methyl group; m represents the number of spacer groups, which is a positive integer of 6 to 11; R2 is a C1 to C12 n-alkyl or n-alkoxy group, a nitro group, a cyano group, or a carboxyl group; R3 is a hydrogen atom or a cyano group; n represents the degree of polymerization (number of repeating units), preferably an integer of 25 to 250, that is, the molecular weight of the polymer is between 10,000 and 100,000, and the polymerization methods include but are not limited to traditional free radical polymerization (initiated by initiators such as azobisisobutyronitrile and benzoyl peroxide), atom transfer radical polymerization (ATRP active polymerization), ring-opening metathesis polymerization (ROMP), reversible addition-fragmentation chain transfer (RAFT active polymerization), etc.
[0010] Specifically, the present invention uses a photoresponsive polymer or a complex thereof with a liquid crystal small molecule for alcohol and acetic acid concentration detection, such as Figure 1 As shown, a thin film for detection is first prepared, and the general steps are similar to the preparation methods disclosed in Chinese invention patent applications CN202010135620.1 and CN202111434432.X:
[0011] (1) Whether it is a photoresponsive polymer or a liquid crystal composite obtained by combining a liquid crystal small molecule with a photoresponsive polymer, it should first be prepared into a solution with a mass fraction of 2.5% to 5%, and the solvent is an organic solvent such as tetrahydrofuran (THF) and dichloromethane. If a liquid crystal composite is required, different proportions of the repeating units in the photoresponsive polymer and the liquid crystal small molecules are mixed according to the molar ratio of the repeating units in the photoresponsive polymer;
[0012] (2) forming a thin film on a substrate by spin coating, drop coating or the like of a solution of a photoresponsive polymer or a liquid crystal composite thereof, leaving the film at room temperature for several hours until all the solvent on the surface of the film is evaporated, and then storing the film away from light;
[0013] (3) Photopatterning of the film. Since light can cause photoresponsive polymers to undergo cis-trans isomerization, they will usually transform from trans to cis when exposed to short-wavelength light, and then revert from cis to trans when exposed to long-wavelength light. In this process, due to the difference in surface tension between trans and cis, an optical mask with a periodic grating structure can be used to achieve a periodic structure of alternating "trans-cis-trans-cis", thus forming a special functional surface with a surface tension gradient of "low surface tension-high surface tension-low surface tension-high surface tension".
[0014] In this process, the film treated in step (2) can be directly photopatterned, or pre-illumination can be added before photopatterning. Since the latter can enhance the effect of film solvent response, that is, the structural color is more obvious, the present invention preferably adopts a method with a pre-illumination step to detect the solution concentration. The method of pre-illumination before photopatterning is: first apply global shorter wavelength illumination to the film to transform it from a trans-rich state to a cis-rich state, and then apply global longer wavelength illumination to restore it to a trans-rich state.
[0015] (4) Soak the film treated in step (3) in an alcohol or acetic acid solution, take out the film after a period of time, blow dry the liquid on the film surface, and observe the surface structural color of the film. The homopolymer film formed by the photoresponsive polymer will be driven by the Maracas flow of the solvent, thereby causing mass migration; the composite film formed by the liquid crystal composite will cause mass migration due to its own surface tension gradient, and both can form surface undulation gratings. Since the surface structural colors of the films obtained from solutions of different concentrations with the same immersion time are different, the concentration of ethanol or acetic acid in the solution can be distinguished.
[0016] The principle of solution concentration detection in the present invention is similar to that recorded in CN202010135620.1 and CN202111434432.X. If a homopolymer film is used for detection, the direction of the Maragni flow of the solvent is from cis to trans, thereby driving the flow of the homopolymer cis to trans. In this process, the mass migration of the film is passive; if a composite film is used for detection, under the action of the solvent, the spontaneous flow induced by the surface tension gradient will dominate, and the composite will flow from trans to cis. This Maragni flow from the area with low surface tension to the area with high surface tension is caused by the active mass migration of the film.
[0017] The solvent in step (1) includes but is not limited to THF and dichloromethane. As long as the photoresponsive polymer and the liquid crystal small molecules can be completely dissolved to obtain a uniform solution, it can be used for subsequent light patterning and alcohol concentration detection. Regarding the mixing ratio of the photoresponsive polymer and the liquid crystal small molecules, preferably, the molar ratio of the repeating unit in the photoresponsive polymer to the liquid crystal small molecules should be in the range of 1:1 to 15:1.
[0018] The substrate in step (2) includes, but is not limited to, hard materials such as silicon wafers and quartz wafers, as well as flexible materials such as polyester (PET), polyimide (PI), polyethylene (PE), etc. The thickness of the film formed on the substrate is preferably 100 to 500 nm, and the surface tension of the photoresponsive polymer therein will change under light.
[0019] During the pre-illumination process of step (3), since the trans-state azobenzene polymer has a greater absorption intensity in the ultraviolet light band, the shorter wavelength light applied is usually 300-400nm ultraviolet light, and the power density during illumination is 100-300mW / cm 2 The illumination time is 10 to 60 seconds, which ensures that the azobenzene in the area irradiated by ultraviolet light has completed the transformation from trans to cis and reached the equilibrium of photoisomerization, which can be considered as a cis-rich state. At this time, the main absorption range of the polymer is 400 to 600nm, and visible light in this range is selected for irradiation. The power density during illumination is 50 to 100mW / cm 2The illumination time is 10 to 60 seconds, ensuring that the azobenzene in the area exposed to visible light has recovered from cis to trans and reached a trans-rich state.
[0020] The optical mask used in the photopatterning process of step (3) is generally a light-proof chromium layer evaporated on quartz glass, which is called a chrome plate. Another common mask is the film mask. The difference is that the chrome plate has higher precision and is more expensive, while the film plate has lower precision and is cheaper. It is preferred to use a one-dimensional grating mask, in which the widths of the light-transmitting and non-light-transmitting areas in the grating are both between 5 and 50 μm. In the embodiment of the present invention, a one-dimensional grating mask chrome plate is used, and its grating parameters are 100LPMM, that is, the period is 10 μm, and the widths of the light-transmitting and non-light-transmitting areas are both 5 μm. When performing photopatterning, short-wavelength light is used for irradiation, and the wavelength is usually 300 to 400 nm. The power density during illumination is 100 to 300 mW / cm 2 The illumination time is between 10 and 30 seconds to ensure that the azobenzene isomerization in the light-transmitting area reaches a cis-rich state when exposed to ultraviolet light.
[0021] When testing the alcohol or acetic acid concentration in step (4), a standard concentration of ethanol or acetic acid solution can be used as a reference, and the difference in the structural color of the film surface can be observed after immersion for the same time to perform semi-quantitative testing.
[0022] The present invention links the macroscopic phenomenon reflected by the periodic surface micro-nanostructure - the structural color visible to the naked eye - with the solution concentration detection, and provides a simple and rapid method for detecting the concentration of alcohol and acetic acid. The concentration difference of the solution can be directly observed without complex system devices and quantitative characterization, and the alcohol concentration can still be detected when the ethanol volume fraction is only 1%, with high resolution. Therefore, this method can be used to semi-quantitatively test whether the concentration of the wine produced by the winery meets the standard and whether the disinfectant produced by the health institution is qualified. Moreover, this detection method is very simple to operate, suitable for large-scale promotion in the industrial field, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 . Schematic diagram of the process of detecting the concentration of alcohol or acetic acid solution of the present invention.
[0024] Figure 2 .Photos of the structural color effects of the PM6AzC4 film in Example 1 after being immersed in alcohol solutions of different concentrations for 2 minutes, where: (a) is 70% ethanol by volume, (b) is 80% ethanol by volume, and (c) is 90% ethanol by volume.
[0025] Figure 3.Photos of the structural color effects of the PM6AzC4 film in Example 2 after being immersed in alcohol solutions of different concentrations for 5 minutes, where: (a) is 40% ethanol volume fraction, (b) is 50% ethanol volume fraction, and (c) is 60% ethanol volume fraction.
[0026] Figure 4 .Photos of the structural color effects of the PM6AzC4 film in Example 3 after being immersed in acetic acid solutions of different concentrations for 5 minutes, where: (a) is 40% acetic acid volume fraction, (b) is 50% acetic acid volume fraction, and (c) is 60% acetic acid volume fraction.
[0027] Figure 5 .Photos of the structural color effects of the PM6AzC4:5CB=5:1 liquid crystal composite film in Example 4 after being immersed in alcohol solutions of different concentrations for 5 minutes, where: (a) is an ethanol volume fraction of 20%, (b) is an ethanol volume fraction of 30%, and (c) is an ethanol volume fraction of 40%.
[0028] Figure 6 .Photos of the structural color effects of the PM6AzC4:5CB=5:1 liquid crystal composite film in Example 5 after being immersed in alcohol solutions of different concentrations for 10 minutes, where: (a) is 5% by volume ethanol, (b) is 10% by volume ethanol, and (c) is 20% by volume ethanol.
[0029] Figure 7 .Photos of the structural color effects of the PM6AzC4:5CB=5:1 liquid crystal composite film in Example 6 after being immersed in different solutions for 30 minutes, where: (a) is ethanol with a volume fraction of 1%, and (b) is pure water.
[0030] Figure 8 .Photos of the effect of PM6AzC4:5CB=5:1 liquid crystal composite film in Example 7 before, during and after spraying disinfectant, where: (a) is before spraying disinfectant, (b) is during spraying disinfectant, and (c) is after spraying disinfectant. DETAILED DESCRIPTION
[0031] To further illustrate the technical means and effects of the present invention, the following will be described in detail in conjunction with the preferred embodiments of the present invention and the accompanying drawings.
[0032] Example 1
[0033] 1. Material selection
[0034]
[0035] The photoresponsive polymer used in this embodiment has a spacer length of m=6, an end group R2 of n-butyl, and a main chain of a methyl methacrylate type azobenzene homopolymer, denoted as PM6AzC4, with a molecular weight of 3.3×10 4 , the polydispersity coefficient is 2.30, and the T g is 76℃, after full exposure to ultraviolet light, T g is 5℃.
[0036] 2. Film Preparation
[0037] PM6AzC4 polymer was prepared into a 5wt% THF solution, stirred overnight and filtered with a filter head, and spin-coated on a clean silicon wafer surface at a spin-coating rate of 3000r / min and a spin-coating time of 30s to obtain a film with a thickness of about 400-500nm. The film was placed in a room temperature and dark environment, and the THF was completely evaporated for several hours to complete the preparation of the film.
[0038] 3. Pre-illumination and light patterning
[0039] The film was pre-irradiated with UV light (365 nm, intensity 151.5 mW / cm 2 , duration 60s) and green light illumination (530nm, intensity 49.5mW / cm 2 , duration is 60s). After pre-illumination, the azobenzene in the film is in a disordered state. Even with green light illumination, it can only achieve the recovery from cis to trans. Without heating, there is no assembly of liquid crystal texture, but it is in an amorphous state. This amorphous state has stronger fluidity and easier mass migration than the liquid crystal state.
[0040] Then, an optical mask with a grating structure containing both the transparent and non-transparent regions with a width of 5 μm was placed on the film surface and irradiated with ultraviolet light (365 nm, intensity 151.5 mW / cm 2 , duration is 15s), at this time the film is in a state of alternating trans and cis arrangements, that is, the same surface has both areas with high surface tension and areas with low surface tension.
[0041] 4. Soak in alcohol solutions of different concentrations
[0042] The film treated in step 3 was immersed in ethanol / water mixed solvents with ethanol volume fractions of 70%, 80%, and 90% for 2 minutes, and then the film was taken out and the solvent on the film surface was blown dry, and the following observations were made: Figure 2The effect photos of the structural color shown in the figure, (a), (b), (c) are the cases where the volume fraction of ethanol is 70%, 80%, and 90% respectively. As the volume fraction of ethanol increases, the structural color of the film after immersion becomes more and more obvious, from a faint structural color appearing at 70%, to a gradually developed and perfect structural color at 80%, and then to a very significant structural color at 90%, so the concentration of ethanol in the alcohol solution can be judged by observing the structural color.
[0043] Example 2
[0044] 1. Material selection
[0045] Same as Example 1.
[0046] 2. Film Preparation
[0047] Same as Example 1.
[0048] 3. Pre-illumination and light patterning
[0049] Same as Example 1.
[0050] 4. Soak in alcohol solutions of different concentrations
[0051] The film treated in step 3 was immersed in ethanol / water mixed solvents with ethanol volume fractions of 40%, 50%, and 60% for 5 minutes, and then the film was taken out and the solvent on the film surface was blown dry, and the following observations were made: Figure 3 The effect photos of structural color shown in the figure, (a), (b), (c) are the cases where the volume fraction of ethanol is 40%, 50%, and 60% respectively. As the volume fraction of ethanol increases, the structural color of the film after immersion becomes more and more obvious. At 40%, the film after immersion has no structural color. At 50%, the structural color is more obvious but not yet fully developed. At 60%, the structural color is very obvious. Therefore, the concentration of ethanol in the alcohol solution can be judged by observing the structural color.
[0052] Example 3
[0053] 1. Material selection
[0054] Same as Example 1.
[0055] 2. Film Preparation
[0056] Same as Example 1.
[0057] 3. Pre-illumination and light patterning
[0058] Same as Example 1.
[0059] 4. Soak in acetic acid solutions of different concentrations
[0060] The film treated in step 3 was immersed in acetic acid / water mixed solvents with acetic acid volume fractions of 40%, 50%, and 60% for 5 minutes, and then the film was taken out and the solvent on the film surface was blown dry, and the following observations were made: Figure 4 The effect photos of structural color shown in (a), (b), and (c) are the cases where the volume fraction of acetic acid is 40%, 50%, and 60%, respectively. When the volume fraction of acetic acid is 40%, there is only a faint structural color, when the volume fraction of acetic acid is 50%, the structural color is more obvious, and when the volume fraction of acetic acid is 60%, the structural color is very significant, so the concentration of acetic acid can be judged by observing the structural color.
[0061] Example 4
[0062] 1. Material selection
[0063]
[0064] In addition to the photoresponsive polymer PM6AzC4 used in Example 1, a liquid crystal small molecule 5CB is also used. It is a common room temperature nematic liquid crystal with a melting point of 20°C and a clearing point of 36.5°C.
[0065] 2. Film Preparation
[0066] PM6AzC4 polymer and 5CB were prepared into 5wt% THF solution respectively, and mixed according to the molar ratio of PM6AzC4 repeating unit to liquid crystal small molecule of 5:1. PM6AzC4 polymer solution needs to be stirred overnight and filtered with a filter head to obtain a liquid crystal composite solution. The mixed composite solution was spin-coated on the surface of a clean silicon wafer at a spin-coating rate of 3000r / min and a spin-coating time of 30s to obtain a film with a thickness of about 400-500nm. Place it in a room temperature and dark environment, wait for several hours for THF to completely evaporate, and the film preparation is completed.
[0067] 3. Pre-illumination and light patterning
[0068] Same as Example 1.
[0069] 4. Soak in alcohol solutions of different concentrations
[0070] The film treated in step 3 was immersed in ethanol / water mixed solvents with ethanol volume fractions of 20%, 30%, and 40% for 5 minutes, and then the film was taken out and the solvent on the film surface was blown dry, and the following observations were made: Figure 5 The photos of the structural color effect shown in (a), (b), and (c) are the cases where the volume fraction of ethanol is 20%, 30%, and 40%, respectively. When the volume fraction of ethanol is 20%, the structural color of the film after immersion is very weak, when the volume fraction is 30%, the structural color is relatively obvious, and when the volume fraction is 40%, the structural color is very obvious. Therefore, the concentration of ethanol in the alcohol solution can be judged by observing the structural color.
[0071] Example 5
[0072] 1. Material selection
[0073] Same as Example 4.
[0074] 2. Film Preparation
[0075] Same as Example 4.
[0076] 3. Pre-illumination and light patterning
[0077] Same as Example 1.
[0078] 4. Soak in alcohol solutions of different concentrations
[0079] The film treated in step 3 was immersed in ethanol / water mixed solvents with ethanol volume fractions of 5%, 10%, and 20% for 10 minutes, and then the film was taken out and the solvent on the film surface was blown dry, and the following observations were made: Figure 6 The effect photos of structural color shown in the figure, (a), (b), (c) are the cases where the volume fraction of ethanol is 5%, 10%, and 20% respectively. As the volume fraction of ethanol increases, the structural color of the film after immersion becomes more and more obvious. At 5%, the structural color of the film after immersion is very weak, at 10%, the structural color is slightly obvious, and at 20%, the structural color is very obvious. Therefore, the concentration of ethanol in the alcohol solution can be judged by observing the structural color.
[0080] Example 6
[0081] 1. Material selection
[0082] Same as Example 4.
[0083] 2. Film Preparation
[0084] Same as Example 4.
[0085] 3. Pre-illumination and light patterning
[0086] Same as Example 1.
[0087] 4. Soak in solutions of different concentrations
[0088] The film treated in step 3 was immersed in a 1% ethanol / water mixed solvent and pure water for 30 minutes, then the film was taken out and the solvent on the film surface was blown dry, and the following observations were made: Figure 7 The effect photos of structural color shown in the figure are (a) for 1% ethanol volume fraction and (b) for pure water. The structural color of the film surface after immersion in 1% ethanol is very obvious, while the structural color of the film surface after immersion in pure water is very weak. Therefore, it is possible to judge whether a trace amount of ethanol is added to the test solution by observing the structural color.
[0089] Example 7
[0090] 1. Material selection
[0091] Same as Example 4.
[0092] 2. Film Preparation
[0093] Same as Example 4.
[0094] 3. Pre-illumination and light patterning
[0095] Same as Example 1.
[0096] 4. Spray disinfectant on the film surface
[0097] Spray disinfectant on the surface of the film treated in step 3, such as Figure 8 As shown, before spraying the disinfectant, the structural color on the film surface was very weak. About 20 to 30 seconds after spraying the disinfectant, the structural color on the film surface was very obvious, indicating that the film responds to the disinfectant very quickly and can be used to detect the ethanol concentration in the disinfectant.
Claims
1. A method for rapidly detecting alcohol or acetic acid concentration, comprising the following steps: 1) preparing a photoresponsive polymer or a complex thereof with a liquid crystal small molecule into a solution with a mass fraction of 2.5% to 5% using an organic solvent; 2) forming a thin film on a substrate using the photoresponsive polymer solution or composite solution prepared in step 1); 3) Directly photopatterning the film, or pre-illuminating the film and then photopatterning the film; 4) Soaking the film patterned in step 3) in alcohol or acetic acid solutions of different concentrations, taking out the film after a period of time, and blowing the liquid on the surface of the film dry. Since the film surface structural colors obtained by using alcohol or acetic acid solutions of different concentrations for the same soaking time are different, the concentration of ethanol or acetic acid in the solution can be distinguished; Wherein, the photoresponsive polymer is selected from one of the polymers having the molecular structures shown in Formula I to Formula IV: Wherein, R1 is a hydrogen atom or a methyl group; m is a positive integer of 6 to 11; R2 is a C1 to C12 n-alkyl group or n-alkoxy group, nitro group, cyano group or carboxyl group; R3 is a hydrogen atom or a cyano group; n is a positive integer representing the degree of polymerization; The liquid crystal small molecules are 4-cyano-4'-pentylbiphenyl and / or 4-cyano-4'-octylbiphenyl.
2. The method according to claim 1, characterized in that In Formula I to Formula IV, n is an integer of 25 to 250, and the molecular weight of the photoresponsive polymer is 10,000 to 100,000.
3. The method according to claim 1, characterized in that In step 1), the photoresponsive polymer and the liquid crystal small molecules are mixed according to a molar ratio of the repeating unit in the photoresponsive polymer to the liquid crystal small molecules of 1:1 to 15:1 to prepare a composite solution with a mass fraction of 2.5% to 5%.
4. The method according to claim 1, characterized in that Step 2) forming a thin film with a thickness of 100 to 500 nm on the substrate and storing it away from light.
5. The method according to claim 1, characterized in that Step 3) The method for photo-patterning the film is: placing an optical mask with a periodic grating structure on the surface of the film and irradiating it with short-wavelength light; the method for pre-illumination before photo-patterning is: first applying global shorter-wavelength light to the film to transform it from a trans-rich state to a cis-rich state, and then applying global longer-wavelength light to restore it to the trans-rich state.
6. The method according to claim 5, characterized in that The shorter wavelength light used in the pre-illumination in step 3) is ultraviolet light with a wavelength of 300 to 400 nm, and the longer wavelength light is visible light with a wavelength of 400 to 600 nm; ultraviolet light with a wavelength of 300 to 400 nm is used in the light patterning.
7. The method according to claim 6, characterized in that Step 3) During pre-illumination, the intensity of the shorter wavelength illumination is 100-300 mW / cm 2 The illumination duration is 10 to 60 seconds; the illumination intensity of the longer wavelength is 50 to 100 mW / cm 2 The illumination duration is 10 to 60 seconds. During light patterning, the illumination intensity is 100 to 300 mW / cm 2 , the lighting duration is 10 to 30 seconds.
8. The method according to claim 5, characterized in that In step 3), a one-dimensional grating mask is used for light patterning, and the widths of the light-transmitting area and the non-light-transmitting area in the grating are both 5 to 50 μm.
9. The method according to claim 1, characterized in that Step 4) When testing the alcohol or acetic acid concentration, a standard concentration of ethanol or acetic acid solution is used as a reference. After immersion for the same time, the difference in the structural color of the film surface is observed to semi-quantitate the ethanol or acetic acid concentration.
Citation Information
Patent Citations
Preparation method and application of solvent-induced photoresponse polymer surface micro-nano structure
CN111333023A
A method for preparing micro / nano structures on the surface of a liquid crystal small molecule-assisted photoresponsive polymer.
CN114196056B
Preparation method of light / pH-sensitive amphiphilic azobenzene polymer micelles
CN103193989A
Acetic acid gas sensor based on azobenzene compound and preparation method and application of acetic acid gas sensor
CN105572174A